Vaginal and Uterine Bacterial Communities in Postpartum Lactating Cows - Clemmons, Brooke A.; Reese, Sydney T.; Dantas, Felipe G.; Franco, Gessica A.; Smith, Timothy P. L.; Adeyosoye, Olusoji I.; Pohler, Ky G.; Myer, Phillip R. (Frontiers in Microbiology, 2017)
Reproductive inefficiency in cattle has major impacts on overall productivity of cattle operations, increasing cost of production, and impacting the sustainability of the cattle enterprise. Decreased reproductive success and associated disease states have been correlated with the presence of specific microbes and microbial community profiles, yet details of the relationship between microbial communities and host physiology are not well known. The present study profiles and compares the microbial communities in the bovine uterus and vagina using 16S rRNA sequencing of the V1-V3 hypervariable region at the time of artificial insemination. Significant differences (p<0.05) between the vaginal and uterine communities were observed at the level of α-diversity metrics, including Chao1, Shannon’s Diversity Index, and observed OTU. Greater clustering of vaginal OTU was apparent in principal coordinate analysis compared to uterine OTU, despite greater diversity in the vaginal community in both weighted and unweighted UniFrac distance matrices (p<0.05). There was a significantly greater relative abundance of unassigned taxa in the uterus (p=0.008), otherwise there were few differences between the overall community profiles. Both vaginal and uterine communities were dominated by Firmicutes, although the relative abundance of rRNA sequences corresponding to species in this phylum was significantly (p=0.007) lower in the uterine community. Additional differences were observed at the genus level, specifically in abundances within Clostridium (p=0.009), Anaerofustis (p=0.018), Atopobium (p=0.035), Oscillospira (p=0.035), 5-7N15 (p=0.035), Mycoplasma (p=0.035), Odoribacter (p=0.042), and within the families Clostridiaceae (p=0.006), Alcaligenaceae (p=0.021), and Ruminococcaceae (p=0.021). Overall, the comparison revealed differences and commonalities among bovine reproductive organs, which may be influenced by host physiology. The increased abundance of unassigned taxa found in the uterus may play a significant biological role in the reproductive status of the animal. The study represents an initial dataset for comparing bacterial communities prior to establishment of pregnancy.